2017
DOI: 10.1371/journal.pone.0180172
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming streets for outdoor play: A process and impact evaluation of “Juega en tu Barrio” (Play in your Neighborhood), an intervention to increase physical activity and opportunities for play

Abstract: BackgroundNew strategies are required to create supportive physical and social environments for children and promote active free-play. Juega en tu Barrio (JETB; Play in your Neighborhood) was designed and implemented to explore the effectiveness of closing a street in a low-to-middle income neighborhood in order to increase children’s outside play and physical activity.MethodsA pretest-posttest design with control group was employed to investigate the intervention effects in a subsample of 100 children, 51 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 47 publications
2
31
0
3
Order By: Relevance
“…Our study found that frequent users of the Ciclovía were more likely to perceive the neighborhood as safe. These results are consistent with studies evaluating Play Streets[42] and active free play[52]. In the “ Juega en tu Barrio” intervention, parents reported an increased perception of safety after the road was closed to traffic[42].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our study found that frequent users of the Ciclovía were more likely to perceive the neighborhood as safe. These results are consistent with studies evaluating Play Streets[42] and active free play[52]. In the “ Juega en tu Barrio” intervention, parents reported an increased perception of safety after the road was closed to traffic[42].…”
Section: Discussionsupporting
confidence: 87%
“…Neighborhood security, traffic perceptions and fear of crime among parents may lead to closer supervision of their children[50] and limiting outdoor recreational opportunities[42,51]. Our study found that frequent users of the Ciclovía were more likely to perceive the neighborhood as safe.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Where parks are insufficient and unsafe, underused city space, such as streets or parking lots, can be enabled and further activated by programs and tactical urbanism. Such strategies have been long used in the region and they were proved to be cost-effective and successful, including: The ciclovía of Bogotá (open streets); Colombian recreovías and "Ecuador Ejercítate" (free outdoors physical activity classes with music); "Juega en tu Barrio" and "CicloRecreoVía" of Chile (streets play and open streets); and new on-road cycle paths 20,21,22 . Such strategies, along with socially inclusive programs, may increase residents sense of safety 23 and, ultimately, reduce health inequalities during the pandemic.…”
mentioning
confidence: 99%
“…[sobre o brincar] é busca pela conquista de autonomia, no sentido da formação de um jeito próprio de perceber o mundo, interpretá-lo, apropriar--se dele e agir, produzindo outros mundos possíveis e resistindo a meios determinantes e pouco criativos de viver. A importância do espaço físico 57 , do ambiente, da paisagem para influenciar positivamente a atividade física entre as crianças e o tempo que se passa ao ar livre vivenciando a cidade estão diretamente relacionados à capacidade da criança de brincar de forma livre 58 (CORTINEZ-O'RYAN, 2017).…”
Section: 2 2 Os Brincares Como Fim Em Siunclassified